Bacterial and Parasitic Co-Infection in Carassius gibelio Bloch, 1782 Caught in the Onaç Reservoir, Türkiye - Yıldırım, P; Kan, Ş; Güçlü, SS; Özmen, Ö; Özdamar, A; Bahrioğlu, E; Kubilay, A (Journal of the Hellenic Veterinary Medical Society, 2024)
This study investigates the bacterial and parasitic co-infection of Prussian carp (Carassius gibelio Bloch, 1782). C. gibelio belongs to the Cyprinidae family, an alien species in the freshwater systems of Turkey. Alien species can cause the emergence of new diseases in native species that constitute the ichthyofauna. C. gibelio specimens were examined from Onaç Reservoir in Burdur, Turkey. Symptoms were skin lesions, exophthalmos, darkening in color, rupture, and hemorrhage in the radius of the caudal fin, and loss of scale of the fish. Gyrodactylus sprostonae and Trichodina sp. were also observed. Additionally, Shewanella putrefaciens and Aeromonas sobria were isolated from the fish specimens. Erosive and ulcerative lesions were frequently seen during the histopathological investigation. Both isolates were resistant to penicillin, oxacillin, lincomycin, and ampicillin. In conclusion, the presence of various bacterial strains, a ciliate parasite, and a monogenic parasite was determined in C. gibelio. We report that the aforementioned fish pathogens created a co-infection in the region. In the future, more study is needed to a clearer awareness of the silver carp dealing with co-infection and the details of the interaction between bacterial and parasitic diseases. This will be beneficial for fish disease management.